An Ontological Inquiry into the Interplay between Igbo-African Culture and the Emergence of Technological Phenomena - Onwuatuegwu, Ignatius Nnaemeka (Journal of Universal Community Empowerment Provision, 2025)
This philosophical exploration examines the emergence of technology in the Igbo-African context. Drawing on philosophical literature and Igbo cultural practices, the paper explores how technology has been understood and used in Igbo society. It considers the role of culture, ethics, and values in shaping the development of technology and highlights the importance of a holistic approach to technology that takes into account the social and cultural context in which it is used. The paper argues that a deeper understanding of the Igbo worldview and philosophy can provide insights into the ethical and social implications of technology and offer a more balanced approach to technology development and implementation. Ultimately, the paper suggests that an engagement with African philosophical traditions can enrich global discussions about technology and contribute to a more diverse and inclusive technological landscape.